Removal of chemicals of concern by high rate nitrifying trickling filters. Issue 12 (15th April 2016) - Mai, Lei; van den Akker, Ben; Du, Jun; Kookana, Rai; Fallowfield, Howard
Abstract: BACKGROUND: The nitrifying trickling filter (NTF) is a process commonly used in wastewater treatment to remove ammonia. What is less clear is its ability to remove emerging organic contaminants. This study evaluated the potential of NTF to remove eight trace organic chemicals of concern (CoCs), with initial concentration of caffeine, bisphenol A, benzotriazole, trimethoprim and acetaminophen 1 mg L −1, atrazine 2 mg L −1, 17α‐ethynylestradiol 5 mg L −1 and N, N‐diethyl‐m‐toluamide 10 mg L −1, using a laboratory‐scale NTF system. The impact of initial nitrification rate on chemicals' removal and the impact of chemicals on nitrification rate were investigated. RESULTS: The removal efficiency of a recirculating NTF for CoC removal was in the following order: caffeine (98%) > acetaminophen and N, N‐diethyl‐m‐toluamide (58.6%) > atrazine (48.7%) > 17α‐ethynylestradiol (48.3%) > benzotriazole (42.8%) > bisphenol A (26.2%) > trimethoprim (17.9%). In NTFs, biodegradation was the dominant process. In this study, the removal of caffeine was found to be the most effective, and removal of trimethoprim the least. The removal efficiency of most chemicals increased, except for benzotriazole, with increasing nitrification. The presence of CoCs might negatively affect nitrification in NTFs. CONCLUSION: The research demonstrated that recirculating high rate NTF is potentially an efficient approach for removal of trace organic contaminants. © 2016 Society of Chemical Industry